Socio-economic Impact of Self Help Group on Members in Banaskantha District of Gujarat - Raut Harshal Ramesh , R. R. Prajapati , Dhara M. Prajapati and M.R. Prajapati, (Indian Journal of Extension Education, 2015)
The ex-post-facto study was undertaken in Banaskantha district of Gujarat state to evaluate the socio-economic impact ofSelf Help Groups on its members. The district comprises of 12 talukas, from which two talukas viz., Palanpur and Deesawas selected purposively as these talukas have more number of SHGs. Alist of women SHGs based on animal husbandryactivities were obtained. Total twelve SHGs, six SHGs from each taluka were selected using simple random sampling.SHG members from each Self Help Group were selected proportionately for making sample size of 120 SHG members asrespondents. Assessment of socio-economic impact was categorized into five aspects viz., (i) Change in income, (ii)Change in spending pattern, (iii) Change in material possession, (iv) Change in thrift habit and (v) Change in employmentof the respondents. Per cent change in income, spending pattern, material possession, thrift habit and employment wasworked out and overall socio-economic impact of SHGs on its members was calculated by summing the score of all fivedimensions of socio-economic impact and converting into per cent change. The study revealed that impact of SHG interms of change in income (38.33 %), change in thrift habit (50.84 %), and change in employment (43.33 %) was foundmedium level of change. While impact of SHG in terms of change in spending pattern (57.50 %) and change in materialpossession (44.16 %) was found low change. It was recorded that 44.17 per cent of the respondent belonged to mediumlevel of change of overall socio-economic impact of SHG on its members. Out of eleven variables, seven variables viz.,education, social participation, occupation, annual income, attitude, innovativeness and media exposure had positive andsignificant association with overall socio-economic impact on members of SHG.